2012
DOI: 10.1088/0957-4484/23/29/294007
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of mercury in field soil and sediment using carboxymethyl cellulose stabilized iron sulfide nanoparticles

Abstract: Mercury (Hg) is one of the most pervasive and bio-accumulative metals in the environment. Yet, effective in situ remediation technologies have been lacking. This study investigated the effectiveness of a class of soil-deliverable FeS nanoparticles for in situ immobilization of Hg in two field-contaminated soils from a New Jersey site and one sediment from an Alabama site. The nanoparticles were prepared using sodium carboxymethyl cellulose (CMC) as a stabilizer. Transmission electron microscopy measurements re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…The dried aggregates were further oven-dried for 6 h at 80°C before use. Sediment analyses were performed by the Soil Testing Laboratory at Auburn University, and the method details have been described elsewhere (Gong et al, 2012). Table S3 gives salient properties of the sediments.…”
Section: Seawater and Sediment Samplesmentioning
confidence: 99%
“…The dried aggregates were further oven-dried for 6 h at 80°C before use. Sediment analyses were performed by the Soil Testing Laboratory at Auburn University, and the method details have been described elsewhere (Gong et al, 2012). Table S3 gives salient properties of the sediments.…”
Section: Seawater and Sediment Samplesmentioning
confidence: 99%
“…FeS has been widely studied for mercury immobilization [15][16][17][18][19]. Liu et al [18] found that the enrichment capacity of FeS could reach 0.75 mol Hg(II) /mol FeS.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the successful formation of CMC-FeS could be only indirectly assessed by verifying the very low polydispersity index, suggesting a quite monodisperse system. In a previous paper on the topic [414], evidence that attachment of CMC onto the surface of FeS particles induced strong electrostatic repulsion between the negatively charged particles was also provided based on zeta potential measurements [414]. Furthermore, when stored in sealed vials under anaerobic conditions at room temperature, the CMC-FeS NP did not display any visual sedimentation over a period of several weeks.…”
Section: Iron Sulphidementioning
confidence: 92%
“…Concerning iron sulphides, very few examples could be retrieved in the literature, dealing with their derivatisation. Among these ones, some [414][415][416] report on iron sulphide which was stabilised by using carboxymethyl cellulose as stabilising ligand. In one case [416], the nanoparticles were prepared using a low-cost, food-grade cellulose (sodium carboxymethyl cellulose, CMC) as the stabiliser.…”
Section: Iron Sulphidementioning
confidence: 99%